FAKTOR-FAKTOR YANG MEMPENGARUHI REMAJA MENGGUNAKAN NARKOBA DI TANGUN KECAMATAN BANGUN PURBA KABUPATEN ROKAN HULU - Hasibuan, Lomoan; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the village of Ancient Build Tangun District of Rokan Hulu in order to determine the factors that affect Adolescent drug use. Problems in this study are (1) Who are the young people who use drugs in Tangun District of Ancient Build? (2) What are the factors that cause remajadi Tangun District of Ancient Build Rokan Hulu taking drugs?.This research is a qualitative descriptive study, the research object in this study based on the police station, then Teens who use drugs. The sampling technique is snoball sampling technique dugunakan as members of the sample chosen specifically based research purposes. To collect the data the researchers used the method of observation, and in-depth interviews using an interview podoman in analyzing research data used in the analysis of qualitative and descriptive writing is described. Based on the research results of this study concluded that the factors that affect adolescents use drugs in the Village District of Build Ancient Tangun Rokan Hulu that personality factors, environmental factors, family factors, educational factors. Keywords: Youth Factor, Using Drugs